Application of the Cooperative Learning Model Using the Type of Group Investigating on Student Learning Outcomes - Anisia Nur Mitha Sari; Mukhamad Murdiono; Elfahmi Lubis (International Journal Labs, 2025)
Educational problems always arise, such as an imbalance between society's demands which change easily compared to the capabilities of educational services. This research aims to test and analyze the relationship between the application of the cooperative learning model and the group investigating type on student learning outcomes. Data collection in this research was carried out by conducting a pre-test and post-test on two treatments, namely the control class and the experimental class, each with 30 students. Data analysis was carried out using the SPSS program, including homogeneity, normality, n-gene tests and hypothesis testing. The research results showed that the posttest scores between the control class and the experimental class showed different scores. The learning outcomes of students in the Pancasila and Citizenship education study program at Muhammadiyah University of Bengkulu improved further after implementing the group investigating learning model. The conclusion of this research shows that the cooperative learning model using group investigating has a positive and significant effect on student learning outcomes.